KONSEP DIRI REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA RUMBAI (PSBR) - Andi Vonda Osada Junike; Jumaini ' '; Wasisto ' Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The phenomenon of adolescent of school dropout in fact has grown old, but is now increasingly becoming the world's attention.. The environmental change experienced by teenage dropouts make a change in the experience of social interaction with the environment and himself. Make them unsafe and not accepted in society. The purpose this research was to descibe self-concept adolescent dropout of school, expecially in the PSBR. That is to view of self-image, ideal self, self-esteem, self roles, self-identity teenage dropouts. This research is a descriptive study with adolescent population in PSBR. The sampling technique in this research is total sampling. The instrument used was a questionnaire while analysis technique using frequency distribution and percentage. Results of the study revealed that most: self-image dropout in PSBR is positive, the ideal self-dropout in the PSBR is positive, the self-esteem dropout in the PSBR is positive, the self roles dropout in the PSBR is positive, the role of self dropout in the PSBR is positive, self-identity dropout in the PSBR is positive. The PSBR is expected to continue to provide coaching so that adolescent self-concept and optimal growing more positive.